The Influence Of Customer Perspectives Related To Business Ethics On Customer Loyalty In The Shopee Market Place - fahrudin; Yuni Safara; Sunaika; Ida Mawaddah (MultiTech Publisher, 2023)
This study aims to determine the effect of a customer perspective on business ethics on customer loyalty in the Shopee marketplace. The results of the study show that having a good customer perspective will lead to increased customer loyalty to the Shopee Marketplace itself. This study uses qualitative research methods with data collection techniques through observation and questionnaires.